Measuring the Administrative Capacity of banks and their impact on Lending Behavior through the Employment determinant (Entrepreneurship Journal for Finance and Business, 2022)
The research aims to measure and analyze the total effect (direct and indirect) between the administrative ability of the research sample banks (the independent variable) and the lending behavior (the dependent variable) through the employment determinant (the mediator variable). 8 commercial banks were used, or 23% of the total listed banks In the Iraqi Stock Exchange of 35 banks for the period (2006-2020). Administrative capacity has an important role in the allocation and diversification of investments, including loans, which have suffered from a high concentration recently due to the low levels of administrative capabilities of the research sample banks.  Management ability was measured and analyzed using Data Envelope Analysis (DEA), and lending behavior was measured by Herfndahl-Hirschman analysis method, and employment was measured by the natural log ratio of the number of employees.  The hypotheses of the study were tested using the statistical program (SmartPLS.v.3.) The research reached a set of results, the most important of which is that there is a significant effect of the administrative ability of the research sample banks in the lending behavior through the employment determinant, and this research concluded with a number of recommendations, the most important of which is the need to pay attention  The research sample banks raise the levels of their administrative capacity because of their positive effects on directing lending behavior through the employment determinant.